The Impact of Local Communities’ Involvement and Relationship Quality on Sustainable Rural Tourism in Rural Area, Sarawak. The Moderating Impact of Self-efficacy - Fong, Sook Fun (Elsevier Ltd., 2014)
Tourism is recognized as a major growth engine for socio-economic development and poverty alleviation especially in rural destinations. Nonetheless, tourism has negative impact on these rural destinations. As a result, local communities’ attitudes and perceptions toward tourism development are one of the important indicators for sustainable tourism development (Choi & Sirakaya, 2006). Besides, people’s belief about their ability to influence the events is important in order to influence the outcomes (Bandura, 1994). Thus, this study attempts to examine the relationship between local communities’ involvement, relationship quality and sustainable rural tourism with self-efficacy as a moderator in the context of tourism industry in Sarawak. The findings of this study will demonstrate a preliminary conceptual framework on local communities’ involvement, relationship quality and sustainable rural tourism and how self-efficacy moderate the relationship between local communities’ involvement, relationship quality and sustainable rural tourism in Sarawak.